Recovery of Variables and Heap Structure in x86 Executables - Balakrishnan, Gogul; Reps, Thomas (University of Wisconsin-Madison Department of Computer Sciences, 2005)
This paper addresses two problems that arise when analyzing executables: (1) recovering variable-like quantities in the absence of symbol-table and debugging information, and (2) recovering useful information about objects allocated in the heap.